If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -5x = -2x + 11 Reorder the terms: 2 + -5x = 11 + -2x Solving 2 + -5x = 11 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2 + -5x + 2x = 11 + -2x + 2x Combine like terms: -5x + 2x = -3x 2 + -3x = 11 + -2x + 2x Combine like terms: -2x + 2x = 0 2 + -3x = 11 + 0 2 + -3x = 11 Add '-2' to each side of the equation. 2 + -2 + -3x = 11 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 11 + -2 -3x = 11 + -2 Combine like terms: 11 + -2 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| x^6-48=0 | | 12z+12y+13z-y= | | N+4n=30 | | 4+4n=-12+2 | | w/2-3(12)=53 | | 8cos^2(x)+4cos(x)-1=0 | | -3x+9=6 | | 16-x/5=x/3 | | 4x(3+x)=16+x | | 6x-5-2x=3y+7-4x | | 7.2a=13.53+2.81a | | y-12=3y-2 | | .12a-.08b=0 | | 5n/3-3/7=61/21 | | 20m+12n-5m+13n+65= | | 5/r-9=8/r+5 | | 4x-24=4x+60 | | 6w-14=4w+24 | | 7x-1=-85 | | 6w-14=4w | | 1/2(2x+54)=1/3(9x+27) | | w/2-3(6)=53 | | 6/7x-3=45 | | (4x+3)/9-(2x+1)/2=0 | | 35+0.10p=25+0.25p | | 0.023X+0.08=0.36X-5.266 | | 35p+0.10=25p+0.25 | | 13b+9-12c= | | 8=g/7 | | 180=2x+(x-8)+x | | -2/5r+2r=1/5r+14/3 | | (4x+3)/9 |